(untitled) (Nordic Journal of African Studies, 2009)
This article articulates the structure of the noun phrase in the Bantu language Nyakyusa. The aim of the study is to move a step ahead from the focus on concords across Bantu languages to the analysis of the order of elements within the noun phrase. As scholars have paid less attention to the syntax of the noun and its dependents (Rugemalira 2007), then the analysis of the order of elements in the Nyakyusa noun phrases is necessary. This study found the following: (i) the dominant attested order of the elements in a Nyakyusa noun phrase is N > [(Poss)(Dem)] > [(Num)(Quant)(A)] > [(Int)(Rel)], (ii) both the possessive and demonstrative may occur immediately after the head noun, but when the possessive immediately follows the head noun it must drop a pre-prefix. Also, the demonstrative can not precede the head noun if so, the meaning changes; (iii) hypothetically, with recurrence, more than seven elements can co-occur within a single noun phrase.